A Review of Phytochemical and Pharmacological Analysis of Poaceae Family Plants (International Journal of Scientific Research in Science and Technology, 2025)
The Poaceae family has 12,000 species of plants and approximately 800 genera. Around 1291 Poaceae family plant species are found in India. Grasses have been utilized since ancient times for nourishment, medicine, ornamental purposes, handcrafts, ceremonies, etc. Some common medicinal grasses like Aristida setacea L., Chrysopogon aciculatus (Retz.) Trin., Chrysopogon zizanioides (L.) Roberty, Cynodon dactylon (L.) pers, Dactyloctenium aegyptium (L.) Willd, Digitaria bicornis (Lam.), and Echinochloa colona (L.). Link, Eragrostis amabilis (L.) Wight & Aen. ex Nees, Eragrostis coarctata (L.), Eulaliopsis binata (Retz.), Hackelochloa granularis (L.) Kuntze, Imperata cylindrica (L.) P. Beauv., Leersia hexandra (Sw.), Oplismenus compositus (L.) P. Beauv., have been extensively used in India. Phytochemicals possess important pharmacological activities like antioxidant, anti-inflammatory, cancer prevention, hormone regulation, immune system support, cardiovascular health, and brain health. Pharmacological activities are important for disease treatment and prevention, drug discovery and development, veterinary medicine, etc. Certain grass species are being used as an ethno-medicine. Number of phytochemical compounds are present which are having excellent pharmacological activity. Saccharum spontaneum L. also used as an ethnomedicine to treat various kinds of disease like microbial infections, gynecological issues, piles, sexual weakness, and burning sensations. Various phytochemicals are reported from Saccharum spontaneum L. leaves, like alkaloids, phenolic compounds, coumarins, and quinones. This plant has been recorded to have numerous pharmacological activities, such as CNS depressant, antipsychotic, antibacterial, antifungal, cytotoxic, antioxidant, anti-inflammatory, and anti-diarrheal. Eulaliopsis binata (Retz.) used to treat digestion problems, skin diseases, wound healing, and bronchitis. This plant has a number of phytochemical components, including alkaloids, triterpenoids, glycosides, phenolic acids, essential oils, etc. Also, this plant species has antioxidant, anti-bacterial, and anti-lithiasis activities. Cynodon dactylon (L.) pers. is also used as a folk treatment for cancer, epilepsy, snakebites, bronchitis, leucoderma, asthma, tumors, and eye disorders. Also this plant contains phytochemicals including terpenoids, resins, phytosterols, reducing sugars, volatile oils, and fixed oils. It has numerous pharmacological activities, including anti-diabetic, anticancer, antimicrobial, antiviral, anti-tumor, anti-infertility, antioxidant, and anti-inflammatory activity.